Analisa Semiotik Terhadap Ragam Hias Rumah di Daerah Between Two Gates, Kampung Alun-Alun, Kotagede - John Felix (Bina Nusantara University, 2020)
Indonesia consists of diverse cultures that have interesting backgrounds. One of them is Javanese culture which until now can be seen through one of them is decorative ornaments from several old houses in the Kotagede area of Jogjakarta. Traditional artists express aesthetic values and communicate messages through the design of house ornaments. This research attempts to read the message implied through home decoration in Kotagede, Jogjakarta with the semiotic method. When traditional artists make decorative ornaments, it seems he is giving a message through visual images or carving. This message seems to originate from their view of life as a result of their interaction with the environment which gives them a way to not only survive but also develop.